Joint associations of multiple leisure-time sedentary behaviours and physical activity with obesity in Australian adults - Salmon Jo; Dunstan David W; Healy Genevieve N; Sugiyama Takemi; Owen Neville (International Journal of Behavioral Nutrition and Physical Activity, 2008)
Abstract Background Television viewing and physical inactivity are independently associated with risk of obesity. However, how the combination of multiple leisure-time sedentary behaviours (LTSB) and physical activity (LTPA) may contribute to the risk of obesity is not well understood. We examined the joint associations of multiple sedentary behaviours and physical activity with the odds of being overweight or obese. Methods A mail survey collected the following data from adults living in Adelaide, Australia (n = 2210): self-reported height, weight, six LTSB, LTPA and sociodemographic variables. Participants were categorised into four groups according to their level of LTSB (dichotomised into low and high levels around the median) and LTPA (sufficient: ≥ 2.5 hr/wk; insufficient: < 2.5 hr/wk). Logistic regression analysis examined the odds of being overweight or obese (body mass index ≥ 25 kg/m2) by the combined categories. Results The odds of being overweight or obese relative to the reference category (low sedentary behaviour time and sufficient physical activity) were: 1.54 (95% confidence interval [CI]: 1.20–1.98) for the combination of low sedentary behaviour time and insufficient physical activity; 1.55 (95% CI: 1.20–2.02) for the combination of high sedentary behaviour time and sufficient physical activity; and 2.26 (95% CI: 1.75–2.92) for the combination of high sedentary behaviour time and insufficient physical activity. Conclusion Those who spent more time in sedentary behaviours (but were sufficiently physically active) and those who were insufficiently active (but spent less time in sedentary behaviour) had a similar risk of being overweight or obese. Reducing leisure-time sedentary behaviours may be as important as increasing leisure-time physical activity as a strategy to fight against obesity in adults.